(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Social work education is the cornerstone of preparing students to address complex social problems with professional competence and ethical sensitivity. As the field of social work develops, it is imperative to understand social work students' attitudes towards the relevance of their studies to real world practice. Aim of the research - to explore social work students' attitudes towards the relevance of their academic studies to real-world social work practice. Research subject - Social work students' attitudes towards the relevance of their studies. Research objectives: 1) identify the relevance of the study; 2) to explore how social work students perceive the relevance of their studies to their future professional practice. The study is based on a quantitative methodology, using a survey questionnaire to collect data from 97 students enrolled in a bachelor's degree programme in social work at a Lithuanian higher education institution. The study used descriptive statistics, correlation analysis and Kruskal-Wallis test to analyse the data. The results showed that students found the study process relevant and meaningful for their personal and professional development. Students generally appreciated the opportunity to apply their knowledge in real-life situations to improve their professional skills. However, state-funded students rated the study process as more relevant than non-state-funded students. The paper concludes that programmes can be attractive to social work students if they are designed and delivered in a way that promotes students' interest in their studies, the application of theory to practice, and support from lecturers and peers. This study contributes to the literature on social work education in higher education by providing insights into social work students' perceptions of the relevance of the study process.